Analýza závislosti vlastního kapitálu a hodnoty stavebních závodů v české ekonomice v letech 2007-2014 - Bahenský, Miloš (Univerzita Pardubice, 2017)
This contribution deals with the problem of business valuation, the issue of forensic engineering and business economics issues. Introductory part of the work deals with the definition of basic concepts such as construction enterprise, equity and enterprise value. The first goal of the submitted contribution is to determine objectified value of the construction enterprises. For a low objectified boundary value is applied Direct Capitalization Method. Afterwards, a very concise description of an income approach valuation technique, just specifically Direct Capitalization Method. The main aim of this contribution is to analyse and compare of equity and the value of construction enterprises in the Czech economy in the years 2007-2014. Research sample (N=35) includes medium and large construction enterprises operating in the Czech Republic. The legal form of construction companies is Public Limited Company and Private Limited Company. These construction enterprises are valued at eight consecutive years. This resulted in a total of 280 values of construction enterprises. Equity is from the same time series, so also in the same number. The data are characterized arithmetic average, minimum and maximum. Statistical methods (the correlation analysis) are used for examining the relation between these indicators. Empirical primary research for data collection is part of the dissertation thesis. In the case of demonstrating statistical correlation data will be the basis for a regression model.
Analysis of the dependence equity and value of construction enterprises in the Czech economyin the years 2007-2014
Keywords: construction enterprise; equity; enterprise value; business valuation; objectified boundary value; Direct Capitalization Method; correlation dependence; G30; G32; M42